The Concept of Intersectionality in Feminist Theory. Issue 5 (May 2014) - Carastathis, Anna
Abstract In feminist theory, intersectionality has become the predominant way of conceptualizing the relation between systems of oppression which construct our multiple identities and our social locations in hierarchies of power and privilege. The aim of this essay is to clarify the origins of intersectionality as a metaphor, and its theorization as a provisional concept in Kimberlé Williams Crenshaw's work, followed by its uptake and mainstreaming as a paradigm by feminist theorists in a period marked by its widespread and rather unquestioned – if, at times, superficial and inattentive – usage. I adduce four analytic benefits of intersectionality as a research paradigm: simultaneity, complexity, irreducibility, and inclusivity. Then, I gesture at some critiques of intersectionality advanced in the last few years, during which the concept has increasingly come under scrutiny.